Towards more efficient, more specific, and safer MRI contrast agents: a Portuguese–French collaborative journey - Pinto, Sara Martinho Almeida; Lacerda, Sara; Morfin, Jean-François; Aroso, Rafael Tiago; Teixeira, Daniela Sofia de Sousa; Garda, Zoltán; Pereira, Maria Miguens; Geraldes, Carlos Frederico Gusmão Campos; Tóth, Éva (Comptes Rendus. Chimie)
Although complexes of the paramagnetic Gd(III) ion have been used with great success for the past 40 years to enhance image contrast in magnetic resonance imaging (MRI), important challenges such as improving the relaxation efficacy, the specificity, the safety, and the environmental impact of these agents remain in this field. Thanks to a collaborative effort between the Centre of Molecular Biophysics in Orléans, France and the Coimbra Chemistry Centre - Institute of Molecular Sciences in Coimbra, Portugal, there have been important advances in the chemistry of MRI probes. The authors have developed rigid, medium-sized, and bishydrated Gd(III) complexes specifically optimized for high-field applications with successful validation in vivo. For the specific targeting of amyloid peptides implicated in many pathologies such as Alzheimer’s disease and diabetes, they have designed benzothiazole-derivative metal chelates with detection potential in MRI, optical, and nuclear imaging modalities. The authors have gained valuable insights into the aggregation behavior of these complexes in solution and how this affects peptide binding affinity. More recently, manganese porphyrin complexes have been investigated with the objective of visualizing the tissue redox state based on the Mn(II)/Mn(III) redox switch, which can be followed not only in classical 1H detection but also in 19F MRI.